Epidemiological Study on Patients Hospitalized in Imam Musa Kazim Hospital, Isfahan, Iran, due to Self-Immolation during the Years 2010-2014 - Mahmoud Keyvanara; Elnaz Kalantari (مجله دانشکده پزشکی اصفهان, 2017)
Background: Self-immolation is among the most damaging types of injuries from burns, causes serious physical injuries and has psychological and economic effects on the person and his or her family. This study assessed the epidemiological characteristics of patients hospitalized in Imam Musa Kazim hospital, Isfahan, Iran, due to self-immolation during a 5-years period.